Inherited Thrombophilia and Pregnancy Complications: Should We Test? - Arachchillage, Deepa R.J.; Makris, Mike (Seminars in Thrombosis and Hemostasis, 2019)
Recurrent miscarriages and pregnancy-related complications cause significant stress to couples looking for successful pregnancy outcome as well as to health care professionals. There is conflicting evidence with respect to the presence and the strength of associations between inherited thrombophilia and these complications. A complete thrombophilia screen is expensive, and no proven effective treatment for women with recurrent miscarriage and inherited thrombophilia is currently available. Based on the concept of microvascular thrombosis of the placenta, women with recurrent miscarriage and placenta-related complications frequently get treated with antithrombotic therapy. In this narrative review, the authors explore the evolving understanding and evidence of inherited thrombophilia in recurrent miscarriages and other pregnancy complications, and whether antithrombotic treatment would modify pregnancy outcome in women with inherited thrombophilia. Finally, they provide some personal recommendations based on available evidence for clinical practice. In summary, inherited thrombophilia testing is not required outside a clinical trial for women with recurrent pregnancy losses or late pregnancy complications. The presence of thrombophilia markers does not generally indicate additional therapy during pregnancy, even if a heritable thrombophilic defect is found in women with recurrent miscarriages or late pregnancy complications.
Keywords: pregnancy; recurrent miscarriage; thrombophilia; low molecular weight heparin; aspirin